Study on the development height of “two zones” under repeated mining of medium-thick coal seams at close range - Zhou, Dong; Wu, Yaowen; Kong, Lingcheng; Liu, Zhongming; Yan, Hongjun; Yang, Ming (Frontiers in Materials, 2026)
IntroductionThe coal faces I0104105 and I0104204 of coal seams 4-1 and 4-2 in the I01 mining area of Shuangma No.1 Mine are taken as the engineering background.Methods In this manuscript, UDEC numerical simulation, similar material simulation, downhole drilling imaging method measurement, and empirical formula calculation methods are employed to address the high development of the “two zones” in close-range medium-thick coal seams during repeated mining. An analysis is conducted on the movement and collapse laws of overlying rocks under the separate mining of 4-1 coal and the repeated mining of 4-1 coal and 4-2 coal. The development height of the “two zones” under repeated mining is determined, compared, and verified against the empirical formulas. Linear analysis is conducted through on-site measurements and empirical formula differences.ResultsThe existing calculation formula coefficients are corrected to propose an empirical formula for the development height of the “two zones” applicable to the Shuangma Mine. The results show that the “two zones” development height presents three significant stages under the repeated mining of medium-thick coal seams at close range: rapid growth, slow growth, and final stability. The height of the “two zones” is not simply added; however, a superposition effect is observed, which is closely related to the physical and mechanical parameters of the rock layers between coal seams, coal seam spacing, and coal seam thickness.DiscussionThe research results have theoretical significance and guiding value for determining the “two zones” height of the overlying rock under repeated mining of medium-thick coal seams at close range.